Occupational and educational structures of the labour force and levels of economic development - Jallade, Jean Pierre; Organisation for Economic Co-operation and Development (Paris] Organisation for Economic Co-operation and Development [London, H.M.S.O.], 1970)
This book provide statistical data about the industry occupational and education structures. It furthers show the relationship between occupation, education and development.
Includes bibliographical references.
asm; 14/02/19
Loans
Keywords: Labor supply; Occupations; Economic development